Healthy Habits Questionnaire Feasibility and Utility for High-Risk Children. (October 2020) - Camp, Nadine L.; Robert, Rebecca C.; Kelly, Katherine P.
The American Academy of Pediatrics provides guidance for pediatric primary care providers to promote healthy weight during childhood. Screening questions on diet and activity habits can help provider assessment and assist counseling for targeted behavior change. We implemented the parent completed, 10-item 5210 Healthy Habits Questionnaire (Ages 2-9 year) in our primary care practice serving low-income minority children with high rates of overweight and obesity. Adherence to the intervention protocol was high, and providers found the content and method of assessment useful for their counseling of individual patients. The aggregate Healthy Habits Questionnaire data provided a snapshot of the health habits in our local clinic population of children, prompting greater awareness for providers and informing their patient care.